Antimicrobial resistance and related gene analysis of Salmonella from egg and chicken sources by whole-genome sequencing - Hu, Lijun (Poult Sci, 2020)
Whole-genome sequencing (WGS) is a valuable tool in research on foodborne pathogens. In this study, a total of 143 isolates of Salmonella serotypes Enteritidis, Typhimurium, and Heidelberg sourced from eggs and chickens were analyzed for their antimicrobial resistance profiles using WGS data. The isolates carried high rate of genes resistant to aminoglycoside (70.63%), tetracycline (26.57%), fosfomycin (25.17%), sulfonamides (23.78%), and β-lactamases (15.38%); and aadA was the most frequently observed antimicrobial resistance gene (ARG). Antimicrobial resistance varies by Salmonella serotypes, with Salmonella enterica serovar Enteritidis (Salmonella ser. Enteritidis) isolates being highly resistant to aminoglycoside (particularly streptomycin); Salmonella ser. Typhimurium more resistant to aminoglycoside, tetracycline, and sulfonamides; and Salmonella ser. Heidelberg more resistant to aminoglycoside and fosfomycin. Salmonella ser. Typhimurium isolates presented more varieties of ARG than Salmonella ser. Enteritidis and Salmonella ser. Heidelberg. Our data showed that 5 isolates of Salmonella ser. Typhimurium and Salmonella ser. Heidelberg contained ARG resistant to ≥ 5 antimicrobials. In addition, 23 Salmonella isolates carried ARG resistant to 4 antimicrobials.